Preaching to the ‘Feral Beast’: Tony Blair’s Farewell Speech to the Press (Altre Modernità, 2010)
This paper, which relies mainly on a cultural studies and critical discourse analytical approach, aims to explore the emotional and discursive space marked out by Tony Blair' Reuters speech on "Public Life" (June 12, 2007) and the heated reaction it received from the British press. Delivered merely a fortnight before the Prime Minister stepped down from office, the speech, which famously  compared the media to "a feral beast" which "hunts in a pack", elaborated on the current crisis of trust affecting both politics and journalism and helped to spark a much needed debate on the ethical and practical challenges facing both 'communities of practice' in order to rekindle civic participation in the political public sphere.